2020
DOI: 10.1097/md.0000000000021731
|View full text |Cite
|
Sign up to set email alerts
|

Cemented versus uncemented hemiarthroplasty for elderly patients with displaced fracture of the femoral neck

Abstract: Background: This meta-analysis was performed to incorporate newly published, high-quality randomized controlled trials (RCTs) to determine the effects of cemented versus uncemented hemiarthroplasty for elderly patients with displaced fracture of the femoral neck. Methods: The following electronic databases were extensively searched from the inception of the database through December 2018: EMBASE, Medline, the Cochrane Library, and Web of Science. RCTs focusing on the ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…The incidence of pulmonary embolism (PE) was statistically significantly higher in the cemented group 535 . Conversely, however, Liu et al, found no difference in cardiovascular complications — including PE — in their meta-analysis of 15 RCT encompassing 3,790 patients comparing cemented vs. cementless hemi-arthroplasty for elderly patients with a displaced femoral neck fracture 536 .…”
Section: - Does the Use Of Pmma Cement During Orthopaedic Procedures ...mentioning
confidence: 95%
“…The incidence of pulmonary embolism (PE) was statistically significantly higher in the cemented group 535 . Conversely, however, Liu et al, found no difference in cardiovascular complications — including PE — in their meta-analysis of 15 RCT encompassing 3,790 patients comparing cemented vs. cementless hemi-arthroplasty for elderly patients with a displaced femoral neck fracture 536 .…”
Section: - Does the Use Of Pmma Cement During Orthopaedic Procedures ...mentioning
confidence: 95%
“…6 There exists considerable controversy among orthopaedic surgeons on the proper management of femoral neck fracture in the elderly cohort with respect to cemented or press-fit prostheses. 3,[6][7][8][9][10][11][12][13][14][15][16][17] In our study, there was a statistically significant difference in age for the press-fit versus cemented arthroplasties, with the press-fit patients being an average of 1.4 years younger. We believe this represents a selection bias in which our surgeons were more likely to treat older patients with a cemented arthroplasty.…”
Section: Discussionmentioning
confidence: 83%
“…The published small RCTs were designed to assess long-term outcomes and show an almost equal longstanding death rate in hip fracture patients treated with cemented or cementless prostheses [1, 11, 17-19, 23, 25, 31]. Despite the lack of perioperative fatalities as a primary endpoint in the RCTs, systematic reviews have based their short-term surgically related death reports on these trials.…”
Section: Discussionmentioning
confidence: 99%